Alkaloid Profiling of Kadamba (Mitragyna speciosa Korth. Havil.) Leaves through Chromatographic Separation and UV-Vis Spectrophotometery Analysis - M. Arifuddin; Fatur Rahman Azmi; Iswahyudi Iswahyudi; Mahfuzun Bone; Harra Ismi Farrah; Hanggara Arifian; Maria Almeida; Arman Rusman; Erwin Samsul; Riki Riki; Hifdzur Rashif Rija'i; Baso Didik Hikmawan; Junaidin Junaidin; Lizma Febrina; Rolan Rusli; Arsyik Ibrahim; Islamudin Ahmad; Herman Herman (Journal of Pharmaceuticals and Natural Sciences, 2025)
Mitragyna speciosa Korth. berasal dari famili Rubiaceae yang banyak tumbuh di daratan negara-negara Asia Tenggara. Tumbuhan ini selain disebut Kratom, khususnya di daerah Kalimantan Timur dikenal juga dengan nama "Kadamba". Mitragyna speciosa Korth. belongs to the Rubiaceae family and is widely found in the mainland of Southeast Asian countries. This plant, known as Kratom, is also referred to as "Kadamba" in East Kalimantan. Kadamba has been used for generations as a traditional medicine and contains predominantly alkaloid compounds, which generally function as analgesics, antitussives, antidiarrheals, adrenergic agents, antimalarials, antibacterials, and antinociceptives. The aim of this research is to determine the isolation and identification methods for alkaloid compounds in Kadamba leaves. In this study, extraction was performed using methanol solvent, followed by fractionation using Vacuum Liquid Chromatography (VLC) and Column Chromatography (CC) with gradient eluents: 100% hexane, n-hexane : Ethyl Acetate (5:1, 1:1, 1:5), 100% Ethyl Acetate, Ethyl Acetate : Methanol (1:1, 1:5), and 100% Methanol. The compounds were then identified using Thin Layer Chromatography (TLC). The isolation process used preparative Thin Layer Chromatography (PTLC) with eluent n-hexane: ethyl acetate: 25% ammonia (6.5:3:0.5 v/v/v), and the spots were observed under UV light at 245 nm and 366 nm. The visible spots were sprayed with Dragendorff's reagent to identify the alkaloid compounds. The results showed that the UV-Vis spectrophotometric characterization of isolate B6-b had two peaks at wavelengths of 288 nm and 294 nm.